Antioxidant activity and phenol content of extracts of bark, stems, and young and mature leaves from Blepharocalyx salicifolius (Kunth) O. Berg - Habermann,E. (2016)
Abstract Phenolic compounds are a group of plant secondary metabolites known to have a variety of bioactivities, including the ability to function as antioxidants. Because of the side effects of the use of synthetic substances, the search for natural and less toxic compounds has increased significantly. This study was designed to evaluate the antioxidant activity and phenol content of hexane, ethyl acetate, and aqueous extracts of the bark (suber) and stems as well as the young and mature leaves of Blepharocalyx salicifolius. The extracts were obtained by extraction with organic solvents and subsequent fractionation by chromatographic partition coefficient. Preliminary tests for the presence of antioxidants were performed using bioautography in thin-layer chromatography. The antioxidant activity of the extracts was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and the phenol content of the extracts was quantified using the Folin-Ciocalteu technique. The results showed that 9 of the 12 extracts evaluated displayed very strong antioxidant activity and three displayed moderate activity. Aqueous extracts of the young leaves and bark and the ethyl acetate extract of the young leaves showed the highest levels of antioxidant activity and total phenolic content (TPC). A correlation was observed between TPC and antioxidant activity index (AAI) with a correlation coefficient (r2) of 0.7999. Thus, the high phenol content of B. salicifolius extracts and its correlation with antioxidant activity provide substrates for further studies.